A broad meta-scientific overview of ethical aspects in Brazilian research on Web, Hypermedia and Multimedia at the WebMedia symposium - Carvalho, Luiz Paulo (2023)
The inaugural meeting of the Workshop on Multimedia and Hypermedia Systems, now known as WebMedia, took place in 1995, one year after the founding of the World Wide Web Consortium (W3C). While the tram was still departing the station, Brazil boarded it. However, Tim Berners-Lee offers harsh criticism of the Web’s effects, applications, and uses three decades after he lay the Web’s conceptual cornerstone. Such as false information, widespread manipulation, the unethical use and exploitation of personal information, corporate monopolies, and dangers to democracy. He followed and kept abreast of the moral implications of the Web. However, did WebMedia also stay up in this context? We followed the Systematic Literature Review methodology with the aim to answer how WebMedia research published between 2005 and 2022 explicitly incorporates ethics. We analyzed 1331 papers, 52 (≈4%) presented ethical aspects, and, from these, one stood out. We concluded that the ethical aspects remained tiny, considering the time coverage. Less than 10% of the publications presented some ethical aspects, including the respective research. The occurrences of Ethics Committee, Informed Consent, or a combination of both did not reach 2% of the publications. Even though the Web and Multimedia are cross-cutting themes in technical and non-technical aspects, the first is dominant. In contrast, the deliberations related to the second are limited, as well as on Ethics or Morals. Therefore, we propose guidelines for community appreciation, embracing a culture of ethical aspects. Our main contribution is bringing a meta-research perspective on ethical aspects dedicated to WebMedia.